2021
DOI: 10.7150/thno.56266
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic enhancement of tendon-to-bone healing via anti-inflammatory and pro-differentiation effects caused by sustained release of Mg2+/curcumin from injectable self-healing hydrogels

Abstract: Poor healing response after rotator cuff reconstruction is multifactorial, with the inflammatory microenvironment and deficiency of stem cell differentiation factors at the lesion site being most relevant. However, there is a lack of effective tissue engineering strategies that can simultaneously exert anti-inflammatory and pro-differentiation effects to promote rotator cuff healing. Methods: In this study, we synthesized and characterized a novel active drug delivery vector that succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 69 publications
(44 reference statements)
1
41
0
Order By: Relevance
“…Interestingly, in another study, liposomal curcumin released from the three-dimensional printed scaffold showed significant cytotoxicity toward in vitro osteosarcoma cells, whereas it promoted osteoblast cell viability, and proliferation (Sarkar and Bose, 2019). Moreover, the composite hydrogel loading with Mg 2+ and curcumin could simultaneously exert anti-inflammatory and pro-differentiation effects to accelerate rotator cuff healing (Chen et al, 2021).…”
Section: Curcuminmentioning
confidence: 97%
“…Interestingly, in another study, liposomal curcumin released from the three-dimensional printed scaffold showed significant cytotoxicity toward in vitro osteosarcoma cells, whereas it promoted osteoblast cell viability, and proliferation (Sarkar and Bose, 2019). Moreover, the composite hydrogel loading with Mg 2+ and curcumin could simultaneously exert anti-inflammatory and pro-differentiation effects to accelerate rotator cuff healing (Chen et al, 2021).…”
Section: Curcuminmentioning
confidence: 97%
“…The biomechanical test and histological results of the rat rotator cuff tear model at 8 weeks after surgery showed that the hydrogel adhesive significantly enhanced the healing of the rotator cuff tendon‐bone interface. [ 120 ] Moreover, another study found that injection of ECM hydrogel into the achilles tendon defect in rats can promote the healing of the Achilles tendon. [ 118 ]…”
Section: Specific Design Principles Of Hydrogel Wound Adhesives For D...mentioning
confidence: 99%
“…[ 145 ] Second, in addition to loading autologous chondrocytes, hydrogel adhesives can also promote cartilage repair by loading other biologically active ingredients (such as drugs, cytokines, and metal ions, etc.). [ 119,120,145 ] For instance, researchers loaded kartogenin (KGN; can induce BMSCs into chondrocytes) into the acrylated hyaluronic acid (m‐HA) hydrogel adhesive (Figure 10C), and in vitro study showed that KGN had a chondrogenesis effect on SMSCs, and in vivo studies showed its potential role for cell homing, especially for recruiting the host's endogenous cells (SMSCs and BMSCs), and promote the production of the tissue similar to cartilage. [ 145 ] In summary, because the mechanical strength and abrasion resistance of existing hydrogel adhesives are difficult to meet the needs of maintaining the normal function of cartilage.…”
Section: Specific Design Principles Of Hydrogel Wound Adhesives For D...mentioning
confidence: 99%
“…Very recently, injectable and self-healing hydrogel comprising Mg 2+ /curcumin was used to treat rotator cuff injury [213]. Starting materials were quaternized chitosan (QCS) and Pluronic Âź F127 (PF127-CHO).…”
Section: Self-healing Hydrogels In Cartilage and Bone Tissue Engineeringmentioning
confidence: 99%